Studi Literasi Sains Fisika dan Kemandirian Belajar Siswa di Tiga Kecamatan di Lombok Timur - Laxmi Zahara; Made Hery Santosa; I Wayan Widiana (Postgraduate, University of Mataram, 2025)
This study aims to analyze the physics science literacy and self-regulated learning of high school students in three sub-districts in East Lombok and their relationship. The research uses a descriptive quantitative method. Quantitative data were obtained through a physics science literacy test and a self-regulated learning questionnaire. A total of 91 students were selected using stratified random sampling. The results show that students' physics science literacy is at a moderate level with an average score of 49 (range 39–77). In terms of self-regulated learning, 38% of students were in the moderate category (score 36–54), and 2% were in the low category (score 18–35). Pearson correlation analysis revealed a positive relationship between physics science literacy and self-regulated learning, with a weak to moderate strength (r = 0.17–0.43; p < 0.05). Factors influencing both include the suboptimal use of learning materials, weak study habits, lack of parental support, and the ineffective implementation of self-regulated learning strategies. In conclusion, collaboration between teachers, schools, and parents is needed to create an environment that supports the improvement of science literacy and self-regulated learning among students.